2019
DOI: 10.1111/1475-6773.13223
|View full text |Cite
|
Sign up to set email alerts
|

The role of plan choice in health care utilization of high‐deductible plan enrollees

Abstract: Objective:To study whether the negative association between enrollment in highdeductible plans and health care utilization is driven by reverse moral hazard or favorable selection, by examining adults with and without a choice of plans. Data Source: 2011-2016 Medical Expenditure Panel Survey Household Component data on nonelderly adults enrolled in employer-sponsored insurance. Study Design: Four types of plans were examined: high-deductible health plans (HDHPs), consumer-directed health plans (CDHPs), low-ded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…The studies included in this theme investigated consequences such as the utilization of health services, health costs, health related behavior, the choice of insurance plan, and the opinion and acceptance of consumers using quantitative, qualitative, review, and theoretical approaches (model-based), the results of quantitative studies are reported in narrative form as follows: modest to high reduction in health services and medications utilization [ 9 , 20 , 21 , 23 , 33 , 38 , 44 , 45 , 47 , 49 , 51 , 55 , 56 , 64 , 69 , 71 ], reduction in health cost [ 21 , 39 , 41 , 42 , 44 , 53 , 65 , 68 ], low or no significant effect on health services utilization [ 6 , 34 , 35 , 40 , 62 , 63 , 65 ], low or no significant effect on health costs [ 5 ], increasing cost contaminate incentive (CCI) [ 57 ], significant correlation with higher preventive behavior [ 13 , 50 ] modest efficiency gain [ 18 ], increasing medication adherence [ 48 ], increasing demand for low price drug [ 61 ], optimal insurance [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies included in this theme investigated consequences such as the utilization of health services, health costs, health related behavior, the choice of insurance plan, and the opinion and acceptance of consumers using quantitative, qualitative, review, and theoretical approaches (model-based), the results of quantitative studies are reported in narrative form as follows: modest to high reduction in health services and medications utilization [ 9 , 20 , 21 , 23 , 33 , 38 , 44 , 45 , 47 , 49 , 51 , 55 , 56 , 64 , 69 , 71 ], reduction in health cost [ 21 , 39 , 41 , 42 , 44 , 53 , 65 , 68 ], low or no significant effect on health services utilization [ 6 , 34 , 35 , 40 , 62 , 63 , 65 ], low or no significant effect on health costs [ 5 ], increasing cost contaminate incentive (CCI) [ 57 ], significant correlation with higher preventive behavior [ 13 , 50 ] modest efficiency gain [ 18 ], increasing medication adherence [ 48 ], increasing demand for low price drug [ 61 ], optimal insurance [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reported negative consequences are as follows: Decreasing the utilization of both necessary and unnecessary care [ 44 , 55 , 71 ], substitution effect from cares with cost-sharing to free care or with lower cost sharing [ 18 , 70 ], and vulnerability of low-income groups [ 49 , 60 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…27 These patients may favorably select HDHPs because of their healthier status, low health care utilization, and/or a want for lower premiums. 27,28 In contrast, patients with low incomes and/or chronic conditions represent the most concerning population for HDHP coverage. Multiple studies have shown that lower-income families were more likely to report delayed or forgone care due to cost when covered by HDHPs.…”
Section: Discussionmentioning
confidence: 99%